The use of nanoparticles in the treatment of infectious diseases and cancer, dental applications and tissue regeneration: a review - Sobhani-Nasab, Ali; Banafshe, Hamid Reza; Atapour, Amir; Khaksary Mahabady, Mahmood; Akbari, Maryam; Daraei, Abdolreza; Mansoori, Yaser; Moradi Hasan-Abad, Amin (Frontiers in Medical Technology, 2024)
The emergence of nanotechnology as a field of study can be traced back to the 1980s, at which point the means to artificially produce, control, and observe matter on a nanometer level was made viable. Recent advancements in technology have enabled us to extend our reach to the nanoscale, which has presented an unparalleled opportunity to directly target biomolecular interactions. As a result of these developments, there is a drive to arise intelligent nanostructures capable of overcoming the obstacles that have impeded the progress of conventional pharmacological methodologies. After four decades, the gradual amalgamation of bio- and nanotechnologies is initiating a revolution in the realm of disease detection, treatment, and monitoring, as well as unsolved medical predicaments. Although a significant portion of research in the field is still confined to laboratories, the initial application of nanotechnology as treatments, vaccines, pharmaceuticals, and diagnostic equipment has now obtained endorsement for commercialization and clinical practice. The current issue presents an overview of the latest progress in nanomedical strategies towards alleviating antibiotic resistance, diagnosing and treating cancer, addressing neurodegenerative disorders, and an array of applications, encompassing dentistry and tuberculosis treatment. The current investigation also scrutinizes the deployment of sophisticated smart nanostructured materials in fields of application such as regenerative medicine, as well as the management of targeted and sustained release of pharmaceuticals and therapeutic interventions. The aforementioned concept exhibits the potential for revolutionary advancements within the field of immunotherapy, as it introduces the utilization of implanted vaccine technology to consistently regulate and augment immune functions. Concurrently with the endeavor to attain the advantages of nanomedical intervention, it is essential to enhance the unceasing emphasis on nanotoxicological research and the regulation of nanomedications' safety. This initiative is crucial in achieving the advancement in medicine that currently lies within our reach.